(untitled) (Olhares, 2015)
The article presents the guidelines of the playwriting of the Argentinian author Daniel Veronese, contextualizing it inside the historical dynamics from the last decades, on the Argentinian stage from 20th Century. The text relates also the masterpiece of the playwright in his direction practice.